Metagenomic profiling reveals how ecological and processing drivers shape the beef microbiome from farm to fork - Asim ur Rahman; Vincenzo Valentino; José F. Cobo-Díaz; Giuseppina Sequino; Avelino Alvarez Ordóñez; Danilo Ercolini; Francesca De Filippis (Food Research International, 2026)

Double-stranded RNA and reverse transcriptase signatures of endogenous retroviruses after exposure to spaceflight environment related stressors - Michelle Mendiola Pla; Franklin H. Lee; Matthew F. Smith; Alejandro Alvarez Lobo; Thomas E. Diaz; Adam S. Cockrell; Dawn E. Bowles (Life Sciences in Space Research, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Hierarchical soil–plant buffering stabilizes nutrient dynamics in citrus under sustained irrigation with contrasting water chemistries - Alberto Imbernón-Mulero; Victoriano Martínez-Alvarez; Belén Gallego-Elvira; José A. Acosta; José F. Maestre-Valero (Plant and Soil, 2026)
Background and aims The increasing use of non-conventional water resources in Mediterranean agriculture raises concerns regarding nutrient imbalances and the capacity of soils to buffer irrigation-driven chemical inputs. This study evaluated how the soil–plant system stabilizes plant nutritional status under irrigation with contrasting water chemistries. Methods Nutrient dynamics were assessed along the soil–water–plant continuum in a commercial grapefruit ( Citrus x paradisi Macfad) orchard irrigated over seven years with freshwater, desalinated seawater subjected to different reverse osmosis intensities, and blended irrigation waters. Results Irrigation waters exhibited strong chemical contrasts. Freshwater and blended waters, particularly the farmer-managed blend, supplied the highest calcium and magnesium loads, whereas desalinated seawater, especially two-step reverse osmosis desalinated water, provided very low mineral inputs. In contrast, nitrogen, phosphorus, and potassium inputs remained largely dominated by fertilization. Despite these differences, soil nutrient availability showed only moderate divergence among treatments and no consistent vertical amplification. At the plant level, leaf and fruit nutrient concentrations largely converged across irrigation types, with variability mainly driven by seasonal and phenological factors. Stoichiometric analysis further indicated progressive attenuation of nutrient contrasts from water to soil and ultimately to plant tissues. Conclusions Our findings are consistent with a hierarchical filtering process in which soil buffering and plant regulation jointly decouple irrigation water chemistry from plant nutritional status. Irrigation water composition alone was therefore insufficient to predict crop nutrient balance, highlighting that the agronomic impact of unconventional irrigation depends on the interaction between water chemistry, soil properties, and fertigation practices.

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

Characterization of microbial diversity, chemical hazards and antimicrobial resistant bacteria in wash water from a fresh-cut vegetable processing plant - Ángel Francés; Mercedes López; Montserrat González-Raurich; José F. Cobo-Díaz; Miguel Prieto; Ana Allende; María I. Gil; Pilar Truchado; Avelino Alvarez-Ordóñez; Márcia Oliveira (International Journal of Food Microbiology, 2026)

Choosing the best washing condition could be crucial in metabolomic analyses of frozen-thawed brown bear sperm - Cristina Palacin-Martinez; Rafael Montes-Garrido; Mercedes Alvarez; Marta Neila-Montero; David Ramírez-González; Victoria Diez-Zavala; Cristina Soriano-Úbeda; Luis Anel-Lopez; Santiago Borragán; Patricia Manrique-Revuelta; Paulino de Paz; Luis Anel; et al. (Animal Reproduction Science, 2026)

Plant growth-promoting bacteria mitigate drought stress in a new forage oat variety (Avena sativa AV25T) - Carolina Pachón-Venegas; Gabriela Toro-Tobón; Paola Delgadillo-Duran; Roxana Yockteng; Fagua Alvarez-Flórez; Daniel F. Rojas-Tapias; German A. Estrada-Bonilla (Plant and Soil, 2026)
Background and Aims Climate change is posing a major threat to global agricultural productivity. Plant growth-promoting bacteria (PGPB) have emerged as sustainable tools to enhance crop tolerance to abiotic stress through different mechanisms. This study aimed to evaluate the physiological, biochemical, and transcriptomic responses of the Altoandina oat variety ( Avena sativa AV25T) under water deficit and to determine the effectiveness of PGPB inoculation. Methods Six PGPB strains were evaluated: Azospirillum brasilense D7, Pseudomonas fluorescens N7, Herbaspirillum sp. AP21, Bacillus subtilis XT13, Priestia megaterium XT14, and B. amyloliquefaciens XT17. Altoandina oat seedlings were inoculated with individual or dual suspensions and drought stress was induced by suspending irrigation. Physiological and biochemical parameters, including stomatal conductance, chlorophyll content, biomass, proline, soluble sugars, and antioxidant enzyme activities, were measured. Transcriptomic profiling was performed on plants subjected to mild water deficit to identify gene expression changes associated with drought response and PGPB inoculation. Results Water deficit significantly affected oat physiology, reducing stomatal conductance and chlorophyll content while inducing the accumulation of osmoprotectants and activation of antioxidant enzymes. N7 and XT17 inoculation mitigated these effects, improving water retention, photosynthetic efficiency, enhanced proline and sugar accumulation compared to non-inoculated controls. Transcriptomic analysis revealed a coordinated activation of genes involved in developmental, signaling, and photosynthetic pathways under mild stress. Conclusions This study demonstrates that selected PGPB strains can enhance drought recovery in the Altoandina oat variety through physiological and biochemical adjustments. Further multi-omics studies are needed to elucidate the molecular mechanisms underlying these beneficial interactions.

Genetic testing for hereditary breast and ovarian cancer in the Murcian population using a comprehensive NGS panel - Y. Mestre Terkemani; L. Rosado Jiménez; A. García Aliaga; M. D. Sarabia Meseguer; M. Marín Vera; J. A. Macías Cerrolaza; P. Sánchez Henarejos; M. R. García Hernández; M. Zafra Poves; B. Alvarez Abril; E. García Torralba; C. B. López Sánchez; et al. (Familial Cancer, 2026)

Mermaids in pools: Ex-situ conservation as a cornerstone for sirenian management worldwide - D.N. Castelblanco-Martínez; E.A. Ramos; A. Alvarez-Aleman; L. von Fersen; R.S. Amaral; F.L.N. Attademo; J.C.G. Borges; L.J. Cabrias-Contreras; D. Caicedo-Herrera; T. Calleson; V.L. Carvalho; A. Dávila-Peñaloza; et al. (Journal for Nature Conservation, 2026)

Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

In-depth characterization of microbiome and resistome of carcasses and processing environments in a swine slaughterhouse - Chiara Manfreda; Sergio Ghidini; Alessandro Fuschi; Daniel Remondini; Flavia Guarneri; Giovanni Loris Alborali; Elena Fernández-Trapote; Jose F. Cobo-Dìaz; Avelino Alvarez-Ordóñez; Adriana Ianieri (Veterinary Microbiology, 2026)

Superchilling storage reduces the growth and diversity of bacterial communities associated with Atlantic salmon (Salmo salar) fillets - P. Collin; M. Darsonval; O. Rué; F.T. Ndoye; G. Alvarez; F. Dubois-Brissonnet (Food Research International, 2026)

Lettuce Growth Under Desalinated Seawater Irrigation: Effects on Yield, Nutrient Uptake, and Soil Properties - A. Imbernón-Mulero; V. Martínez-Alvarez; B. Gallego-Elvira; J. A. Acosta; J. F. Maestre-Valero (Journal of Soil Science and Plant Nutrition, 2025)
The use of non-conventional water sources, such as desalinated seawater (DSW), for agricultural irrigation is increasing in arid and semi-arid regions, raising concerns about potential impacts on crop physiology, productivity, and soil health. This study assessed the agronomic effects of DSW irrigation on iceberg lettuce ( Lactuca sativa var. capitata ) grown over four consecutive seasons in outdoor pallet boxes. Three water quality treatments were compared: (i) freshwater (FW; control); (ii) DSW sourced from a reverse osmosis coastal desalination plant; and (iii) a 50:50 blend of FW and DSW (MW). Results indicated no significant differences in morphological traits or plant growth across irrigation types, with average lettuce hearts weights of 771.3 ± 55.9 g, meeting commercial standards. However, nutrient uptake varied significantly among irrigation resources and growing cycles. Principal component analysis and hierarchical clustering grouped nutrient concentrations in roots, hearts, and outer leaves into distinct clusters, highlighting seasonal influences and water-quality-driven nutrient availability. Nutrient uptake in plants irrigated with MW closely resembled plants irrigated with DSW, while FW irrigation showed greater divergence. Additionally, soil analyses revealed differential accumulation of boron, sodium and chloride, linked to the chemical composition of each water source. Despite these differences, optimized fertilization effectively mitigated nutrient imbalances (e.g., nitrogen, phosphorus, potassium, calcium and magnesium), ensuring comparable crop performance across treatments. This study demonstrates that DSW is a feasible irrigation resource for iceberg lettuce cultivation, provided that nutrient management is carefully adjusted and soil quality is continuously monitored to mitigate potential long-term risks of desalinated waters. Graphical Abstract

Elucidating the neuromeric organization of the Mongolian gerbil brain - F. Lucero-Arteaga; S. Labegorra; A. Abrego-Alvarez; V. Heck; A. I. Portu; M. A. Boeris; A. Alonso; B. Ribeiro Do-Couto; M. Á. García-Cabezas; K. Y. Tseng; José Luis Ferran (Brain Structure and Function, 2025)
The Mongolian Gerbil ( Meriones unguiculatus ) diverged from rats/mice around 45 million years ago and developed adaptations to extreme temperatures and water scarcity. Another feature of the Mongolian Gerbils is their social monogamy similar to that of prairie voles. These observations suggest that there are potential differences in the Mongolian Gerbil brain that are distinct from that of rats and mice. The goal of the present study is to establish the extent to which the neuromeric organization of the brain is conserved in the Mongolian Gerbil and to gain insights on how evolutionary expansion and diversification of brain regions occur across species. Our data shows that the multineuromeric origin of tyrosine hydroxylase-positive processes in the Mongolian Gerbil is similar to that in mice and rats, spanning from the diencephalon, midbrain, and the rostral hindbrain. There are also observable anatomical differences. However, most of the components characteristic of these neuromeres are identifiable in the Mongolian gerbil, closely mirroring those found in mice and rats. Together, these findings suggest that the conserved neuromeric organization likely stems from a restricted genetic toolset that began in the Muridae family 45 million years ago, and that a profound reorganization of the fundamental structural plan delineating the neuromeric segmentation is not required for the emergence of diverse functionality among species of phylogenetically related families. Future studies are needed to establish how the genetic programs within each neuromeric unit are influenced by environmental factors that ultimately impact the size of the neuromeric derivatives and their functional connectivity.

Diverse Acinetobacter in retail meat: a hidden vector of novel species and antimicrobial resistance genes, including plasmid-borne bla, mcr-4.3 and tet(X3) - Alba Puente; José F. Cobo-Díaz; Márcia Oliveira; Rebeca Cordero-García; Filipa Grosso; Francesco Asnicar; Nicola Segata; Yara El dessouky; Mercedes López; Miguel Prieto; Luísa Peixe; Avelino Alvarez-Ordóñez (International Journal of Food Microbiology, 2025)

OS01-07 Ochratoxin A and its possible role in Parkinson's Disease: a computational study spotlighting the potential mechanisms of action - L. Pedroni; F. Perugino; C. Dall'Asta; L. Alvarez Erviti; A. Mally; A. Vettorazzi; L. Dellafiora (Toxicology Letters, 2025)

Insights into the virome of the Andean blackberry (Rubus glaucus) in Ecuador - Raúl Cifuentes; Juan F. Cornejo-Franco; Robert A. Alvarez-Quinto; Dimitre Mollov; Anibal Martínez; José Ochoa; Dan E. V. Villamor; Ioannis E. Tzanetakis; Diego F. Quito-Avila (European Journal of Plant Pathology, 2025)

Transmembrane protein 95 as a promising molecular marker of ram sperm functionality - Cristina Palacin-Martinez; Mercedes Alvarez; Cristina Soriano-Úbeda; Luis Anel-Lopez; Rafael Montes-Garrido; Marta Neila-Montero; Paulino de Paz; Luis Anel; Marta F. Riesco (Theriogenology, 2025)

Native Australian seedlings exhibit novel strategies to acclimate to repeated heatwave events - Philippa R. Alvarez; Rosalie J. Harris; Alicia M. Cook; Verónica F. Briceño; Adrienne B. Nicotra; Andrea Leigh (Oecologia, 2025)
Heatwaves are becoming more intense and frequent. Plant photosystem thermal thresholds can vary with species, but also shift in response to environmental triggers. Both upper and lower thresholds can acclimate to repeated heatwaves through ecological stress memory, where prior exposure primes them for subsequent events. The extent to which acclimation to repeated heat stress events varies among environmental origin and/or species is unknown. Different acclimation strategies might reflect biome of origin, or may be species-specific. For 12 species from two contrasting biomes—extreme desert and benign coastal temperate—we investigated responses to two simulated heatwaves, via shifts in upper and lower critical temperatures of photosystem II, and the difference between these thresholds, thermal tolerance breadth (TTB). Biome of origin had no effect on thermal tolerance. Observed differences among species following heat events suggested two possible acclimatory strategies. In some cases, species increased thermal thresholds during the first heatwave, but at the cost of reduced thermal tolerance during the second heatwave, a sprinter strategy. Other species acclimated to the first heatwave and further increased thermal tolerance to a second heatwave, indicative of ecological stress memory, a marathoner strategy. Synthesis: these among-species responses to heatwaves could suggest distinct vulnerabilities and resilience to repeat heat stress events, with some species having limited capacity to tolerate consecutive heatwaves, possibly as the cost of acclimation is too great, with other species having the advantage of increased tolerance via stress memory, helping them survive future stress, at least in the short-term.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Investigation of nuclide inventory of cladding material irradiated in the Goesgen PWR core - R. Dagan; T. König; M. Herm; F. Alvarez; E. Dorval; S. Häkkinen; E. Vlassopoulos; A. Shama; A. Smaizys; P. Schillebeeckx (Annals of Nuclear Energy, 2025)

Neat ammonia use in a heavy-duty diesel engine converted to spark ignition focused on lean operation - Luis F. Alvarez; Cristopher J. Ulishney; Omid Askari; Cosmin E. Dumitrescu (Fuel, 2025)

Carbon, nitrogen, and noble gas isotopes reveal deep volatile signatures in thermal springs in the Central Volcanic Zone (CVZ) of the Andes - PH Barry; JM de Moor; MW Broadley; AM Seltzer; DV Bekaert; K Patil; CGE Bartels; ED Young; BE Longworth; B Barosa; A Bastianoni; D Bastoni; et al. (Earth and Planetary Science Letters, 2025)

Impacts of an organophosphate pesticide and water restriction on physiology and immunity in the passerine Zonotrichia capensis - Benjamín Corvalan; Felipe Alvarez-Vergara; Diego Landaeta; Natalia Ramirez-Otarola; Juan Carlos Sanchez-Hernandez; Karin Maldonado; Roberto F. Nespolo; Seth D. Newsome; Pablo Sabat (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Loss of cognitive function in Mexican children due to lead exposure and the associated economic costs - Jose Luis Figueroa; Alejandra Rodríguez-Atristain; Luis F. Bautista-Arredondo; Carolina Lerma Treviño; Martín Romero Martínez; Belem Trejo Valdivia; Sandra V. Avalos-Alvarez; Jorge Eduardo Sánchez-Morales; Richard Fuller; Sergio Bautista-Arredondo; Martha M. Téllez-Rojo (Environmental Research, 2024)

Osteosarcoma cells exhibit functional interactions with stromal cells, fostering a lung microenvironment conducive to the establishment of metastatic tumor cells - Matías J. P. Valenzuela Alvarez; Luciana M. Gutierrez; Juan M. Bayo; María J. Cantero; Mariana G. Garcia; Marcela F. Bolontrade (Molecular Biology Reports, 2024)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P02-44 Robotic device for fully automated high-content screening on C. elegans as a novel NAMs platform for DART assessment - L. Mouchiroud; E. Katsyuba; M. Bourgeois; L. Stojkovic; H. Alvarez Sanchez; F. Tâche; M. Cornaglia (Toxicology Letters, 2024)

Pre-pubertal obesity compromises ovarian oxidative stress, DNA repair and chemical biotransformation - Kelsey Timme; M. Estefanía González-Alvarez; Aileen F. Keating (Toxicology and Applied Pharmacology, 2024)

Complete genome sequence and phylogenetic analysis of a newly discovered fusagra-like virus infecting Carica papaya in Ecuador - Juan F. Cornejo-Franco; Edison Reyes-Proaño; Robert A. Alvarez-Quinto; Francisco J. Flores; Diego F. Quito-Avila (Archives of Virology, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Integrating fishers’ knowledge on fish use with ecological networks to assess the ‘silent threat’ of mercury contamination in tropical marine and freshwater fisheries - Paula Evelyn Rubira Pereyra; Andrés Ospina‑Alvarez; Márcia Caroline Friedl Dutra; Bárbara Heck Schallenberger; Gustavo Hallwass; Alpina Begossi; Mariana Clauzet; Priscila F. M. Lopes; Renato Azevedo Matias Silvano (Environment, Development and Sustainability, 2024)

Exposure to 7,12-dimethylbenz[a]anthracene impacts ovarian DNA damage sensing and repair proteins differently in lean and obese female mice and weight loss may mitigate obesity-induced ovarian dysfunction - M. Estefanía González-Alvarez; Imaobong Inyang; Aileen F. Keating (Toxicology and Applied Pharmacology, 2024)

Laminar burning velocity of Ammonia/Air mixtures at high pressures - Luis F. Alvarez; James Shaffer; Cosmin E. Dumitrescu; Omid Askari (Fuel, 2024)

Regional assessment of the historical trends of mercury in sediment cores from Wider Caribbean coastal environments - Yoelvis Bolaños-Alvarez; Ana Carolina Ruiz-Fernández; Joan-Albert Sanchez-Cabeza; Misael Díaz Asencio; Luisa F. Espinosa; Juan Pablo Parra; Jesús Garay; Ramón Delanoy; Nicolás Solares; Katia Montenegro; Alexis Peña; Fabiola López; et al. (Science of The Total Environment, 2024)

Evaluation of the Treatment with Akkermansia muciniphila BAA-835 of Chemotherapy-induced Mucositis in Mice - Ramon O. Souza; Vivian C. Miranda; Mônica F. Quintanilha; Bruno Gallotti; Samantha R. M. Oliveira; Janayne L. Silva; Jacqueline I. Alvarez-Leite; Luís C. L. Jesus; Vasco Azevedo; Kátia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

An inexpensive paracetamol sensor based on an acid-activated carbon fiber microelectrode - Diego Bolaños-Méndez; Jocelyne Alvarez-Paguay; Lenys Fernández; Pablo F. Saavedra-Alulema; Moris S. Veloz-Romero; Patricio J. Espinoza-Montero (Chemosphere, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

An extension of the characteristic curve model of plant species behavior in heavy metal soils - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; María E. Gálvez; Rodrigo Rojas; Fernando A. Alvarez; Vicente Zetola; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

Characteristic curve modeling of plant species behavior in soils with heavy metals - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; Fernando A. Alvarez; Vicente Zetola; Luis H. Pereira; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

A review of limitations and potentials of desalination as a sustainable source of water - Babak Zolghadr-Asli; Neil McIntyre; Slobodan Djordjevic; Raziyeh Farmani; Liliana Pagliero; Victoriano Martínez-Alvarez; José F. Maestre-Valero (Environmental Science and Pollution Research, 2023)
For centuries, desalination, in one way or another, has helped alleviate water scarcity. Over time, desalination has gone through an evolutionary process influenced largely by available contemporary technology. This improvement, for the most part, was reflected in the energy efficiency and, in turn, in terms of the cost-effectiveness of this practice. Thanks to such advancements, by the 1960s, the desalination industry experienced notable exponential growth, becoming a formidable option to supplement conventional water resources with a reliable non-conventional resource. That said, often, there are pressing associated issues, most notably environmental, socioeconomic, health, and relatively recently, agronomic concerns. Such reservations raise the question of whether desalination is indeed a sustainable solution to current water supply problems. This is exceptionally important to understand in light of the looming water and food crises. This paper, thus, tends to review these potential issues from the sustainability perspective. It is concluded that the aforementioned issues are indeed major concerns, but they can be mitigated by actions that consider the local context. These may be either prophylactic, proactive measures that require careful planning to tailor the situation to best fit a given region or reactive measures such as incorporating pre- (e.g., removing particles, debris, microorganisms, suspended solids, and silt from the intake water prior to the desalination process) and post-treatments (e.g., reintroducing calcium and magnesium ions to water to enhance its quality for irrigation purposes) to target specific shortcomings of desalination.

Sequencing-based analysis of the microbiomes of Spanish food processing facilities reveals environment-specific variation in the dominant taxa and antibiotic resistance genes - Adrián Alvarez-Molina; José F. Cobo-Díaz; Elena A. Alexa; Fiona Crispie; Miguel Prieto; Mercedes López; Paul D. Cotter; Avelino Alvarez-Ordóñez (Food Research International, 2023)

Achieving coherence between the Marine Strategy Framework Directive and the Maritime Spatial Planning Directive - Th. Paramana; M. Dassenakis; N. Bassan; C. Dallangelo; P. Campostrini; S. Raicevich; F. Ronchi; G. Giorgi; A. Murillas-Maza; M.C. Uyarra; N. Papadopoulou; C. Smith; et al. (Marine Policy, 2023)

Hepatic and ovarian effects of perfluorooctanoic acid exposure differ in lean and obese adult female mice - M. Estefanía González-Alvarez; Aileen F. Keating (Toxicology and Applied Pharmacology, 2023)

Ovine fertility by artificial insemination in the breeding season could be affected by intraseasonal variations in ram sperm proteomic profile - Marta Neila-Montero; Mercedes Alvarez; Marta F. Riesco; Rafael Montes-Garrido; Cristina Palacin-Martinez; Antonio Silva-Rodríguez; Francisco E. Martín-Cano; Fernando J. Peña; Paulino de Paz; Luis Anel; Luis Anel-Lopez (Theriogenology, 2023)

Response of cows with osteomalacia grazing sub-tropical native pastures to phosphorus supplementation with loose mineral mix or feed blocks - C.O. Schild; F.M. Boabaid; L.G.S. Olivera; J.I. Armendano; A. Saravia; A. Custodio; J. Algorta; C. Alvarez; M. Jaurena; R.M. Dixon; F. Riet-Correa (The Veterinary Journal, 2023)

Susceptibility and transcriptomic response to plasma-activated water of Listeria monocytogenes planktonic and sessile cells - Paula Fernández-Gómez; José F. Cobo-Díaz; Marcia Oliveira; Montserrat González-Raurich; Avelino Alvarez-Ordóñez; Miguel Prieto; James L. Walsh; Morten Sivertsvik; Estefanía Noriega-Fernández; Mercedes López (Food Microbiology, 2023)

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

Addition of β-glucans in diets for tropical gar (Atractosteus tropicus) larvae: effects on growth, digestive enzymes and gene expression of intestinal epithelial integrity and immune system - L. A. Cigarroa-Ruiz; F. J. Toledo-Solís; S. A. Frías-Gómez; R. Guerrero-Zárate; S. Camarillo-Coop; C. S. Alvarez-Villagómez; E. S. Peña-Marín; M. A. Galaviz; R. Martínez-García; C. A. Álvarez-González (Fish Physiology and Biochemistry, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

In vitro–in vivo correlation of drug release profiles from medicated contact lenses using an in vitro eye blink model - Ana F. Pereira-da-Mota; Maria Vivero-Lopez; Piyush Garg; Chau-Minh Phan; Angel Concheiro; Lyndon Jones; Carmen Alvarez-Lorenzo (Drug Delivery and Translational Research, 2023)
There is still a paucity of information on how in vitro release profiles from drug-loaded contact lenses (CLs) recorded in 3D printed eye models correlate with in vivo profiles. This work aims to evaluate the release profiles of two drug-loaded CLs in a 3D in vitro eye blink model and compare the obtained results with the release in a vial and the drug levels in tear fluid previously obtained from an animal in vivo study. In vitro release in the eye model was tested at two different flow rates (5 and 10 µL/min) and a blink speed of 1 blink/10 s. Model CLs were loaded with two different drugs, hydrophilic pravastatin and hydrophobic resveratrol. The release of both drugs was more sustained and lower in the 3D eye model compared to the in vitro release in vials. Interestingly, both drugs presented similar release patterns in the eye model and in vivo, although the total amount of drugs released in the eye model was significantly lower, especially for resveratrol. Strong correlations between percentages of pravastatin released in the eye model and in vivo were found. These findings suggest that the current 3D printed eye blink model could be a useful tool to measure the release of ophthalmic drugs from medicated CLs. Nevertheless, physiological parameters such as the composition of the tear fluid and eyeball surface, tear flow rates, and temperature should be optimized in further studies. Graphical abstract

Identification and genetic characterization of a new totivirus from Bursera graveolens in western Ecuador - Juan F. Cornejo-Franco; Robert A. Alvarez-Quinto; Dimitre Mollov; Diego F. Quito-Avila (Archives of Virology, 2023)

Corrigendum to “An optimized centrifugation protocol for ram sperm ensuring high sample yield, quality and fertility” [Theriogenology 191 (2022) 179–191] - Marta Neila-Montero; Marta F. Riesco; Rafael Montes-Garrido; Cristina Palacin-Martinez; César Chamorro; Paulino de Paz; Mercedes Alvarez; Luis Anel; Luis Anel-Lopez (Theriogenology, 2023)

Evidence of SARS-CoV-2 infection in postmortem lung, kidney, and liver samples, revealing cellular targets involved in COVID-19 pathogenesis - Viviana Falcón-Cama; Teresita Montero-González; Emilio F. Acosta-Medina; Gerardo Guillen-Nieto; Jorge Berlanga-Acosta; Celia Fernández-Ortega; Anabel Alfonso-Falcón; Nathalie Gilva-Rodríguez; Lilianne López-Nocedo; Daina Cremata-García; Mariuska Matos-Terrero; Giselle Pentón-Rol; et al. (Archives of Virology, 2023)
There is an urgent need to understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-host interactions involved in virus spread and pathogenesis, which might contribute to the identification of new therapeutic targets. In this study, we investigated the presence of SARS-CoV-2 in postmortem lung, kidney, and liver samples of patients who died with coronavirus disease (COVID-19) and its relationship with host factors involved in virus spread and pathogenesis, using microscopy-based methods. The cases analyzed showed advanced stages of diffuse acute alveolar damage and fibrosis. We identified the SARS-CoV-2 nucleocapsid (NC) in a variety of cells, colocalizing with mitochondrial proteins, lipid droplets (LDs), and key host proteins that have been implicated in inflammation, tissue repair, and the SARS-CoV-2 life cycle (vimentin, NLRP3, fibronectin, LC3B, DDX3X, and PPARγ), pointing to vimentin and LDs as platforms involved not only in the viral life cycle but also in inflammation and pathogenesis. SARS-CoV-2 isolated from a patient´s nasal swab was grown in cell culture and used to infect hamsters. Target cells identified in human tissue samples included lung epithelial and endothelial cells; lipogenic fibroblast-like cells (FLCs) showing features of lipofibroblasts such as activated PPARγ signaling and LDs; lung FLCs expressing fibronectin and vimentin and macrophages, both with evidence of NLRP3- and IL1β-induced responses; regulatory cells expressing immune-checkpoint proteins involved in lung repair responses and contributing to inflammatory responses in the lung; CD34 + liver endothelial cells and hepatocytes expressing vimentin; renal interstitial cells; and the juxtaglomerular apparatus. This suggests that SARS-CoV-2 may directly interfere with critical lung, renal, and liver functions involved in COVID-19-pathogenesis.

The background microbiota and sanitization agent drive the fate of Listeria monocytogenes in multispecies biofilms formed on a plasma-polymerized coating applied on stainless steel - Paula Fernández-Gómez; Marcia Oliveira; José F. Cobo-Díaz; Montserrat González-Raurich; Rodolfo Múgica-Vidal; Fernando Alba-Elías; Miguel Prieto; Avelino Alvarez-Ordóñez; Mercedes López (International Journal of Food Microbiology, 2023)

Cys mutants as tools to study the oligomerization of the pore-forming toxin sticholysin I - Yadira P. Hervis; Aisel Valle; Liem Canet; Azalia Rodríguez; Maria E. Lanio; Carlos Alvarez; Heinz J. Steinhoff; Isabel F. Pazos (Toxicon, 2023)

Molecular Detection of Rickettsia parkeri Strain Atlantic Rainforest in Ticks Parasitizing Small Mammals in Northeastern Brazil - Josiane M. Rocha; Philipe B. de Oliveira; Sócrates F. da Costa-Neto; Maria H. Ogrzewalska; Thiago F. Martins; João L. H. Faccini; Martin R. D. V. Alvarez; Hermes R. Luz; George R. Albuquerque (Acta Parasitologica, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Krill finder: spatial distribution of sympatric fin (Balaenoptera physalus) and humpback (Megaptera novaeangliae) whales in the Southern Ocean - F. Alvarez; J. L. Orgeira (Polar Biology, 2022)

Trophic variability of long tail hake Macruronus magellanicus in the Southwestern Atlantic: movements evidenced by stomach content and stable isotope analysis - C. D. Alvarez; A. R. Giussi; F. Botto (Polar Biology, 2022)

Genetic diversity of Chlamydia pecorum detected in sheep flocks from Mexico - M. M. Limón-González; R. Hernández-Castro; F. Martínez-Hernández; J. Xicohtencatl-Cortes; H. Ramírez-Alvarez; E. G. Palomares-Resendiz; E. Díaz-Aparicio (Brazilian Journal of Microbiology, 2022)

Characterization of a new potyvirus infecting Thevetia ahouai in Ecuador - Maria G. Cañada-Bautista; Edison G. Reyes-Proaño; Juan F. Cornejo-Franco; Robert A. Alvarez-Quinto; Dimitre Mollov; Diego F. Quito-Avila (Archives of Virology, 2022)

Tetramethyl-phenanthroline copper complexes in the development of drugs to treat cancer: synthesis, characterization and cytotoxicity studies of a series of copper(II)-l-dipeptide-3,4,7,8-tetramethyl-phenanthroline complexes - Natalia Alvarez; Celisnolia M. Leite; Adriana Napoleone; Luis F. S. Mendes; Carlos Y. Fernández; Ronny R. Ribeiro; Javier Ellena; Alzir A. Batista; Antonio J. Costa-Filho; Gianella Facchin (JBIC Journal of Biological Inorganic Chemistry, 2022)

Modulatory Impact of the sRNA Mcr11 in Two Clinical Isolates of Mycobacterium tuberculosis - Karen L. F. Alvarez-Eraso; Laura M. Muñoz-Martínez; Juan F. Alzate; Luis F. Barrera; Andres Baena (Current Microbiology, 2022)

The ghost vampire: spatio-temporal distribution and conservation status of the largest bat in the Americas - F. Alvarez; S. Gomes da Silva; L. M. Guevara-Chumacero; F. Fernandes Ferreira; L. Alvarez Borla; R. Firmino de Sousa; D. P. Silva (Biodiversity and Conservation, 2021)

Expression of miR-34a and miR-15b during the progression of cervical cancer in a murine model expressing the HPV16 E7 oncoprotein - Rodolfo Ocadiz-Delgado; Jose-Luis Cruz-Colin; Elizabeth Alvarez-Rios; Antonio Torres-Carrillo; Karina Hernandez-Mendoza; Juan-Cristobal Conde-Pérezprina; Guadalupe-Isabel Dominguez-Gomez; Enrique Garcia-Villa; Paul F. Lambert; Patricio Gariglio (Journal of Physiology and Biochemistry, 2021)

Using Shapley values to assess the impact of temporary traffic restrictions on NO2 levels in Madrid urban area - F. Alvarez; M. Smith (International Journal of Environmental Science and Technology, 2021)

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

Soil inoculations with Anabaena cylindrica improve aggregate stability and nutrient dynamics in an arable soil and exhibit potential for erosion control - Adriana L. Alvarez; Sharon L. Weyers; Jane M. F. Johnson; Robert D. Gardner (Journal of Applied Phycology, 2021)

Solvent-Assisted Hot Melt Extrusion of a Thermally Labile, High Melting Point Compound - C. Lagan; J. E. Huckle; J. M. Katz; B. Khorsand; D. Daurio; G. P. Andrews; J. Chung; F. Alvarez-Nunez (AAPS PharmSciTech, 2021)

Conservation threats and future prospects for the freshwater fishes of Ecuador: A hotspot of Neotropical fish diversity - Windsor E. Aguirre; Gabriela Alvarez‐Mieles; Fernando Anaguano‐Yancha; Ricardo Burgos Morán; Roberto V. Cucalón; Daniel Escobar‐Camacho; Iván Jácome‐Negrete; Pedro Jiménez Prado; Enrique Laaz; Katherin Miranda‐Troya; Ronald Navarrete‐Amaya; Fredy Nugra Salazar; et al. (Journal of Fish Biology, 2021)
Freshwater fish communities in Ecuador exhibit some of the highest levels of diversity and endemism in the Neotropics. Unfortunately, aquatic ecosystems in the country are under serious threat and conditions are deteriorating. In 2018–19, the government of Ecuador sponsored a series of workshops to examine the conservation status of Ecuador's freshwater fishes. Concerns were identified for 35 species, most of which are native to the Amazon region, and overfishing of Amazonian pimelodid catfishes emerged as a major issue. However, much of the information needed to make decisions across fish groups and regions was not available, hindering the process and highlighting the need for a review of the conservation threats to Ecuador's freshwater fishes. Here, we review how the physical alteration of rivers, deforestation, wetland and floodplain degradation, agricultural and urban water pollution, mining, oil extraction, dams, overfishing, introduced species and climate change are affecting freshwater fishes in Ecuador. Although many of these factors affect fishes throughout the Neotropics, the lack of data on Ecuadorian fish communities is staggering and highlights the urgent need for more research. We also make recommendations, including the need for proper enforcement of existing environmental laws, restoration of degraded aquatic ecosystems, establishment of a national monitoring system for freshwater ecosystems, investment in research to fill gaps in knowledge, and encouragement of public engagement in citizen science and conservation efforts. Freshwater fishes are an important component of the cultural and biological legacy of the Ecuadorian people. Conserving them for future generations is critical.

Up-regulation of pro-angiogenic molecules and events does not relate with an angiogenic switch in metastatic osteosarcoma cells but to cell survival features - Luciana M. Gutiérrez; Matías Valenzuela Alvarez; Yuanzheng Yang; Fiorella Spinelli; María José Cantero; Laura Alaniz; Mariana G. García; Eugenie S. Kleinerman; Alejandro Correa; Marcela F. Bolontrade (Apoptosis, 2021)

Chemical speciation of selected toxic metals and multivariate statistical techniques used to assess water quality of tropical Mexican Lake Chapala - Jorge Omar Murillo-Delgado; Humberto Daniel Jimenez-Torres; Jorge Israel Alvarez-Bobadilla; Jose Antonio Gutierrez-Ortega; Jessica Badillo Camacho; Pedro F. Zárate-del Valle; Icela D. Barcelo-Quintal; Eire Reynaga Delgado; Sergio Gomez-Salazar (Environmental Monitoring and Assessment, 2021)

Recovery disparity between coral cover and the physical functionality of reefs with impaired coral assemblages - F. Javier González‐Barrios; Rafael A. Cabral‐Tena; Lorenzo Alvarez‐Filip (Global Change Biology, 2021)
The ecology and structure of many tropical coral reefs have been markedly altered over the past few decades. Although long‐term recovery has been observed in terms of coral cover, it is not clear how novel species configurations shape reef functionality in impaired reefs. The identities and life‐history strategies of the corals species that recover are essential for understanding reef functional dynamics. We used a species identity approach to quantify the physical functionality outcomes over a 13 year period across 56 sites in the Mexican Caribbean. This region was affected by multiple stressors that converged and drastically damaged reefs in the early 2000s. Since then, the reefs have shown evidence of a modest recovery of coral cover. We used Bayesian linear models and annual rates of change to estimate temporal changes in physical functionality and coral cover. Moreover, a functional diversity framework was used to explore changes in coral composition and the traits of those assemblages. Between 2005 and 2018, physical functionality increased at a markedly lower rate compared to that of coral cover. The disparity between recovery rates depended on the identity of the species that increased (mainly non‐framework and foliose‐digitate corals). No changes in species dominance or functional trait composition were observed, whereas non‐framework building corals consistently dominated most reefs. Although the observed recovery of coral cover and functional potential may provide some ecological benefits, the long‐term effects on reef frameworks remain unclear, as changes in the cover of key reef‐building species were not observed. Our findings are likely to be representative of many reefs across the wider Caribbean basin, as declines in coral cover and rapid increases in the relative abundance of weedy corals have been reported regionally. A coral identity approach to assess species turnover is needed to understand and quantify changes in the functionality of coral reefs.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

A New Approach to Ex Vivo Permeation Studies in In-Situ Film-Forming Systems - Amanda F. Silva-Alvarez; Maíra P. Ferreira; Fabiana T. M. C. Vicentini; Vinicius Pedrazzi; Osvaldo de Freitas (AAPS PharmSciTech, 2020)

Characterization of functionalized bentonite as nanocarrier of salicylic acid with protective action against Pseudomonas syringae in tomato plants - Andrea Y. Mansilla; María F. Salcedo; Silvana L. Colman; Merari T. Chevalier; Matias R. Lanfranconi; Vera A. Alvarez; Claudia A. Casalongué (European Journal of Plant Pathology, 2020)

Enhanced arsenic removal from water by a bimetallic material ZrOx-FeOx with high OH density - Esmeralda Vences-Alvarez; Alejandro Lopez-Valdivieso; Luis F. Cházaro-Ruíz; Horacio Flores-Zuñiga; Jose Rene Rangel-Mendez (Environmental Science and Pollution Research, 2020)

Reef-scale impacts of the stony coral tissue loss disease outbreak - Nuria Estrada-Saldívar; Ana Molina-Hernández; Esmeralda Pérez-Cervantes; Francisco Medellín-Maldonado; F. Javier González-Barrios; Lorenzo Alvarez-Filip (Coral Reefs, 2020)

Medium- and long-term functional behavior evaluations in an experimental focal ischemic stroke mouse model - Juçara Loli de Oliveira; Marina Ávila; Thiago Cesar Martins; Marcio Alvarez-Silva; Elisa Cristiana Winkelmann-Duarte; Afonso Shiguemi Inoue Salgado; Francisco José Cidral-Filho; William R. Reed; Daniel F. Martins (Cognitive Neurodynamics, 2020)

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Thermochronology and exhumation rates of granitic intrusions at Mesa Central, Mexico - Angel F. Nieto-Samaniego; María de Jesús Paulina Olmos-Moya; Gilles Levresse; Susana A. Alaniz-Alvarez; Fanis Abdullin; Alexis del Pilar-Martínez; Shunshan Xu (International Geology Review, 2020)

A model-based exploration of farm-household livelihood and nutrition indicators to guide nutrition-sensitive agriculture interventions - Natalia Estrada-Carmona; Jessica E. Raneri; Stephanie Alvarez; Carl Timler; Shantonu Abe Chatterjee; Lenora Ditzler; Gina Kennedy; Roseline Remans; Inge Brouwer; Karin Borgonjen-van den Berg; Elise F. Talsma; Jeroen C. J. Groot (Food Security, 2020)
Assessing progress towards healthier people, farms and landscapes through nutrition-sensitive agriculture (NSA) requires transdisciplinary methods with robust models and metrics. Farm-household models could facilitate disentangling the complex agriculture-nutrition nexus, by jointly assessing performance indicators on different farm system components such as farm productivity, farm environmental performance, household nutrition, and livelihoods. We, therefore, applied a farm-household model, FarmDESIGN, expanded to more comprehensively capture household nutrition and production diversity, diet diversity, and nutrient adequacy metrics. We estimated the potential contribution of an NSA intervention targeting the diversification of home gardens, aimed at reducing nutritional gaps and improving livelihoods in rural Vietnam. We addressed three central questions: (1) Do ‘Selected Crops’ (i.e. crops identified in a participatory process) in the intervention contribute to satisfying household dietary requirements?; (2) Does the adoption of Selected Crops contribute to improving household livelihoods (i.e. does it increase leisure time for non-earning activities as well as the dispensable budget)?; and (3) Do the proposed nutrition-related metrics estimate the contribution of home-garden diversification towards satisfying household dietary requirements? Results indicate trade-offs between nutrition and dispensable budget, with limited farm-household configurations leading to jointly improved nutrition and livelihoods. FarmDESIGN facilitated testing the robustness and limitations of commonly used metrics to monitor progress towards NSA. Results indicate that most of the production diversity metrics performed poorly at predicting desirable nutritional outcomes in this modelling study. This study demonstrates that farm-household models can facilitate anticipating the effect (positive or negative) of agricultural interventions on nutrition and the environment, identifying complementary interventions for significant and positive results and helping to foresee the trade-offs that farm-households could face. Furthermore, FarmDESIGN could contribute to identifying agreed-upon and robust metrics for measuring nutritional outcomes at the farm-household level, to allow comparability between contexts and NSA interventions.

Climate drives community‐wide divergence within species over a limited spatial scale: evidence from an oceanic island - Antonia Salces‐Castellano; Jairo Patiño; Nadir Alvarez; Carmelo Andújar; Paula Arribas; Juan José Braojos‐Ruiz; Marcelino del Arco‐Aguilar; Víctor García‐Olivares; Dirk N. Karger; Heriberto López; Ioanna Manolopoulou; Pedro Oromí; et al. (Ecology Letters, 2020)
Geographic isolation substantially contributes to species endemism on oceanic islands when speciation involves the colonisation of a new island. However, less is understood about the drivers of speciation within islands. What is lacking is a general understanding of the geographic scale of gene flow limitation within islands, and thus the spatial scale and drivers of geographical speciation within insular contexts. Using a community of beetle species, we show that when dispersal ability and climate tolerance are restricted, microclimatic variation over distances of only a few kilometres can maintain strong geographic isolation extending back several millions of years. Further to this, we demonstrate congruent diversification with gene flow across species, mediated by Quaternary climate oscillations that have facilitated a dynamic of isolation and secondary contact. The unprecedented scale of parallel species responses to a common environmental driver for evolutionary change has profound consequences for understanding past and future species responses to climate variation.

Ralstonia solanacearum, Ganoderma australe, and bacterial wetwood as predictors of ironwood tree (Casuarina equisetifolia) decline in Guam - C. M. Ayin; A. M. Alvarez; C. Awana; F. M. Schleinzer; B. D. Marx; R. L. Schlub (Australasian Plant Pathology, 2019)
Ironwood ( Casuarina equisetifolia subsp. equisetifolia ) trees on Guam have been in decline since 2002. This study applied proportional odds logistic multiple regression modeling to a set of biological variables in order to find significant decline predictors as a first step towards identifying pathogenic contributors. Based on the analysis of a set of 77 medium and large trees, the bacterium Ralstonia solanacearum and the fungus Ganoderma australe species complex were found to be significant predictors, with p values of R. solanacearum by G. australe interaction was not a strong effect, indicating additive rather than multiplicative behavior of these effects on decline severity ( p value>0.087). When nine covariates were applied univariately to a data subset of 30 tree cross-sections, the significance of R. solanacearum was strongly upheld while that of G. australe was moderately reduced. Also significant were percent cross-sectional area with bacterial wetwood and the formation of ooze within 24 h. Wetwood bacteria of Klebsiella spp. and K. oxytoca were found across all levels of decline and were not significant predictors. Other enteric bacteria identified included Kosakonia , Enterobacter, Pantoea, Erwinia, and Citrobacter .

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Assessing Human Health Risks Associated with Consumption of Metal Content in Shrimp from NW Mexico - C. C. Osuna-Martínez; M. G. Frías-Espericueta; B. Y. Ramos-Magaña; M. F. Soto-Jiménez; Y. Brau-Ibarra; L. A. Félix-Salazar; J. I. Osuna-López; M. Aguilar-Juárez; D. Voltolina; C. G. Delgado-Alvarez (Bulletin of Environmental Contamination and Toxicology, 2019)

Developmental changes in oxygen consumption and hypoxia tolerance in the heat and hypoxia‐adapted tabasco line of the Nile tilapia Oreochromis niloticus , with a survey of the metabolic literature for the genus Oreochromis - Warren W. Burggren; Jose F. Mendez‐Sanchez; Gil Martínez Bautista; Emyr Peña; Rafael Martínez García; Carlos A. Alvarez González (Journal of Fish Biology, 2019)
The genus Oreochromis is among the most popular of the tilapiine cichlid tribe for aquaculture. However, their temperature and hypoxia tolerance, if tested at all, is usually tested at temperatures of 20–25°C, rather than at the considerably higher temperatures of 30–35°C typical of tropical aquaculture. We hypothesized that both larvae and adults of the heat and hypoxia‐adapted Tabasco‐line of the Nile tilapia Oreochromis niloticus would be relatively hypoxia‐tolerant. Oxygen consumption rate ( ), Q 10 and aquatic surface respiration (ASR) was measured using closed respirometry at 2 ( c . 0.2 g), 30 ( c . 2–5 g), 105 c . (10–15 g) and 240 ( c . 250 g) days of development, at 25°C, 30°C and 35°C. at 30°C was inversely related to body mass: c . 90 μM O 2 g −1 /h in larvae down to c . 1 μM O 2 g −1 /h in young adults. Q 10 for was typical for fish over the range 25–35°C of 1.5–2.0. ASR was exhibited by 50% of the fish at pO 2 of 15–50 mmHg in a temperature‐dependent fashion. However, the largest adults showed notable ASR only when pO 2 fell to below 10 mmHg. Remarkably, p crit for was 12–17 mmHg at 25–30°C and still only 20–25 mmHg across development at 35°C. These values are among the lowest measured for teleost fishes. Noteworthy is that all fish maintain equilibrium, ventilated their gills and showed routine locomotor action for 10–20 min after ceased at near anoxia and when then returned to oxygenated waters, all fish survived, further indicating a remarkable hypoxic tolerance. Remarkably, data assembled for from >30 studies showed a > x2000 difference, which we attribute to calculation or conversion errors. Nonetheless, p crit was very low for all Oreochromis sp. and lowest in the heat and hypoxia‐adapted Tabasco line.

Biogeochemical recuperation of lowland tropical forest during succession - Benjamin W. Sullivan; Rachel L. DuBose; Megan K. Nasto; Silvia Alvarez‐Clare; Camie M. Dencker; Fiona M. Soper; Kevin T. Shoemaker; F. Yoko Ishida; Joana Zaragoza‐Castells; Eric A. Davidson; Cory C. Cleveland (Ecology, 2019)
High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest establishment. Biogeochemical theory and results from individual studies suggest that N can recuperate during secondary forest recovery, especially relative to P. Here, we synthesized 23 metrics of N and P in soil and plants from 45 secondary forest chronosequences located in the wet tropics to empirically explore (1) whether there is a consistent change in nutrients and nutrient cycling processes during secondary succession in the biome; (2) which metrics of N and P in soil and plants recuperate most consistently; (3) if the recuperation of nutrients during succession approaches similar nutrient concentrations and fluxes as those in mature forest in ~100 yr following the initiation of succession; and (4) whether site characteristics, including disturbance history, climate, and soil order are significantly related to nutrient recuperation. During secondary forest succession, nine metrics of N and/or P cycling changed consistently and substantially. In most sites, N concentrations and fluxes in both plants and soil increased during secondary succession, and total P concentrations increased in surface soil. Changes in nutrient concentrations and nutrient cycling processes during secondary succession were similar whether mature forest was included or excluded from the analysis, indicating that nutrient recuperation in secondary forest leads to biogeochemical conditions that are similar to those of mature forest. Further, of the N and P metrics that recuperated, only soil total P and foliar δ 15 N were strongly influenced by site characteristics like climate, soils, or disturbance history. Predictable nutrient recuperation across a diverse and productive ecosystem may support future forest growth and could provide a means to quantify successful restoration of ecosystem function in secondary tropical forest beyond biomass or species composition.

Microbial Communities of the Gut and Nest of the Humus- and Litter-Feeding Termite Procornitermes araujoi (Syntermitinae) - Edimar A. Moreira; Thabata M. Alvarez; Gabriela F. Persinoti; Douglas Antonio Alvaredo Paixão; Letícia R. Menezes; João P. Franco Cairo; Fabio Marcio Squina; Ana M. Costa-Leonardo; Tiago Carrijo; Alberto Arab (Current Microbiology, 2018)

Determination of Kinetic, Isotherm, and Thermodynamic Parameters of the Methamidophos Adsorption onto Cationic Surfactant-Modified Zeolitic Materials - S. Alvarez-García; J. J. Ramírez-García; F. Granados-Correa; J. C. Sánchez-Meza (Water, Air, & Soil Pollution, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Infection with Micromonospora strain SB3 promotes in vitro growth of Lolium multiflorum plantlets - I. F. Della Mónica; M. V. Novas; L. J. Iannone; G. Querejeta; J. M. Scervino; S. I. Pitta-Alvarez; J. J. Regalado (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

An exudate detection method for diagnosis risk of diabetic macular edema in retinal images using feature-based and supervised classification - D. Marin; M. E. Gegundez-Arias; B. Ponte; F. Alvarez; J. Garrido; C. Ortega; M. J. Vasallo; J. M. Bravo (Medical & Biological Engineering & Computing, 2018)

Detection of honey bee viruses in Argentinian stingless bees (Hymenoptera: Apidae) - L J Alvarez; F J Reynaldi; P J Ramello; M L G Garcia; G H Sguazza; A H. Abrahamovich; M Lucia (Insectes Sociaux, 2018)

A novel Chromatiales bacterium is a potential sulfide oxidizer in multiple orders of marine sponges - Adi Lavy; Ray Keren; Ke Yu; Brian C. Thomas; Lisa Alvarez‐Cohen; Jillian F. Banfield; Micha Ilan (Environmental Microbiology, 2018)
Summary Sponges are benthic filter feeders that play pivotal roles in coupling benthic‐pelagic processes in the oceans that involve transformation of dissolved and particulate organic carbon and nitrogen into biomass. While the contribution of sponge holobionts to the nitrogen cycle has been recognized in past years, their importance in the sulfur cycle, both oceanic and physiological, has only recently gained attention. Sponges in general, and Theonella swinhoei in particular, harbour a multitude of associated microorganisms that could affect sulfur cycling within the holobiont. We reconstructed the genome of a Chromatiales (class Gammaproteobacteria) bacterium from a metagenomic sequence dataset of a T. swinhoei ‐associated microbial community. This relatively abundant bacterium has the metabolic capability to oxidize sulfide yet displays reduced metabolic potential suggestive of its lifestyle as an obligatory symbiont. This bacterium was detected in multiple sponge orders, according to similarities in key genes such as 16S rRNA and polyketide synthase genes. Due to its sulfide oxidation metabolism and occurrence in many members of the Porifera phylum, we suggest naming the newly described taxon Candidatus Porisulfidus .

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Explaining the performance of irrigation communities in a water-scarce region - F. Alcon; P. A. García-Bastida; M. Soto-García; V. Martínez-Alvarez; B. Martin-Gorriz; A. Baille (Irrigation Science, 2017)

UV and visible activation of Cr(III)-doped TiO2 catalyst prepared by a microwave-assisted sol–gel method during MCPA degradation - S. Y. Mendiola-Alvarez; J. L. Guzmán-Mar; G. Turnes-Palomino; F. Maya-Alejandro; A. Hernández-Ramírez; L. Hinojosa-Reyes (Environmental Science and Pollution Research, 2017)

Complete genome sequence of a variant of maize-associated totivirus from Ecuador - Robert A. Alvarez-Quinto; Rodrigo F. Espinoza-Lozano; Carlos A. Mora-Pinargote; Diego F. Quito-Avila (Archives of Virology, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

Association between PNPLA3 (rs738409), LYPLAL1 (rs12137855), PPP1R3B (rs4240624), GCKR (rs780094), and elevated transaminase levels in overweight/obese Mexican adults - Yvonne N. Flores; Rafael Velázquez-Cruz; Paula Ramírez; Manuel Bañuelos; Zuo-Feng Zhang; Hal F. Yee; Shen-Chih Chang; Samuel Canizales-Quinteros; Manuel Quiterio; Guillermo Cabrera-Alvarez; Nelly Patiño; Jorge Salmerón (Molecular Biology Reports, 2016)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Occurrence of maize lethal necrosis in Ecuador: a disease without boundaries? - D. F. Quito-Avila; R. A. Alvarez; A. A. Mendoza (European Journal of Plant Pathology, 2016)

The multidecadal component of the Mediterranean summer variability - M. J. OrtizBevia; A. RuizdeElvira; F. J. Alvarez-Garcia; M. Tasambay-Salazar (Climate Dynamics, 2016)

Organization and mode of action of two component system signaling circuits from the various kingdoms of life - Adrian F. Alvarez; Carlos Barba‐Ostria; Hortencia Silva‐Jiménez; Dimitris Georgellis (Environmental Microbiology, 2016)
Summary Two‐component system (TCS) signaling circuits regulate numerous cellular processes in response to environmental cues in both prokaryotic and eukaryotic cells. These signaling circuits are all based on phosphoryl‐group transfers between histidine and aspartate containing modules of sensor kinase and response regulator proteins. Curiously, the architecture and organization of prokaryotic and eukaryotic two‐component systems reveal notable variations, raising the question of whether the input‐response specificity that governs the majority of prokaryotic TCSs also governs the eukaryotic ones. In this review, we contrast the TCS architecture and signaling circuits of prokaryotes and eukaryotes, and discuss their possible consequences on signaling specificity.

Insights into the genetic structure of the cowpea pest Callosobruchus maculatus in Africa - K. Kébé; N. Alvarez; A. Espíndola; F. Justy; I. Olivieri; M. Sembène (Journal of Pest Science, 2016)

Metagenomic analysis of a high carbon dioxide subsurface microbial community populated by chemolithoautotrophs and bacteria and archaea from candidate phyla - Joanne B. Emerson; Brian C. Thomas; Walter Alvarez; Jillian F. Banfield (Environmental Microbiology, 2016)
Summary Research on geologic carbon sequestration raises questions about potential impacts of subsurface microbiota on carbon cycling and biogeochemistry. Subsurface, high‐ CO 2 systems are poorly biologically characterized, partly because of difficulty accessing high‐volume, uncontaminated samples. CO 2 ‐driven C rystal G eyser ( CG , U tah, USA ), an established geologic carbon sequestration analogue, provides high volumes of deep (∼ 200–500 m) subsurface fluids. We explored microbial diversity and metabolic potential in this high‐ CO 2 environment by assembly and analysis of metagenomes recovered from geyser water filtrate. The system is dominated by neutrophilic, iron‐oxidizing bacteria, including ‘marine’ M ariprofundus ( Z etaproteobacteria ) and ‘freshwater’ Gallionellales , sulfur‐oxidizing T hiomicrospira crunogena and T hiobacillus ‐like Hydrogenophilales . Near‐complete genomes were reconstructed for these bacteria. CG is notably populated by a wide diversity of bacteria and archaea from phyla lacking isolated representatives (candidate phyla) and from as‐yet undefined lineages. Many bacteria affiliate with OD 1, OP 3, OP 9, PER , ACD 58, WWE 3, BD 1‐5, OP 11, TM 7 and ZB 2. The recovery of nearly 100 genes encoding ribulose‐1,5 bisphosphate carboxylase‐oxygenase subunit proteins of the C alvin cycle and AMP salvage pathways suggests a strong biological role in high‐ CO 2 subsurface carbon cycling. Overall, we predict microbial impacts on subsurface biogeochemistry via iron, sulfur, and complex carbon oxidation, carbon and nitrogen fixation, fermentation, hydrogen metabolism, and aerobic and anaerobic respiration.

Genetic and epigenetic differences associated with environmental gradients in replicate populations of two salt marsh perennials - C. M. Foust; V. Preite; A. W. Schrey; M. Alvarez; M. H. Robertson; K. J. F. Verhoeven; C. L. Richards (Molecular Ecology, 2016)
While traits and trait plasticity are partly genetically based, investigating epigenetic mechanisms may provide more nuanced understanding of the mechanisms underlying response to environment. Using AFLP and methylation‐sensitive AFLP , we tested the hypothesis that differentiation to habitats along natural salt marsh environmental gradients occurs at epigenetic, but not genetic loci in two salt marsh perennials. We detected significant genetic and epigenetic structure among populations and among subpopulations, but we found multilocus patterns of differentiation to habitat type only in epigenetic variation for both species. In addition, more epigenetic than genetic loci were correlated with habitat in both species. When we analysed genetic and epigenetic variation simultaneously with partial Mantel, we found no correlation between genetic variation and habitat and a significant correlation between epigenetic variation and habitat in Spartina alterniflora . In Borrichia frutescens , we found significant correlations between epigenetic and/or genetic variation and habitat in four of five populations when populations were analysed individually, but there was no significant correlation between genetic or epigenetic variation and habitat when analysed jointly across the five populations. These analyses suggest that epigenetic mechanisms are involved in the response to salt marsh habitats, but also that the relationships among genetic and epigenetic variation and habitat vary by species. Site‐specific conditions may also cloud our ability to detect response in replicate populations with similar environmental gradients. Future studies analysing sequence data and the correlation between genetic variation and DNA methylation will be powerful to identify the contributions of genetic and epigenetic response to environmental gradients.

Erratum to: An estimation of ENSO predictability from its seasonal teleconnections - M. Tasambay-Salazar; M. J. OrtizBeviá; F. J. Alvarez-García; A. M. RuizdeElvira (Theoretical and Applied Climatology, 2015)

An estimation of ENSO predictability from its seasonal teleconnections - M. Tasambay-Salazar; M. J. OrtizBeviá; F. J. Alvarez-García; A. M. RuizdeElvira (Theoretical and Applied Climatology, 2015)

Human papillomavirus type 16 E7 oncoprotein upregulates the retinoic acid receptor-beta expression in cervical cancer cell lines and K14E7 transgenic mice - Jorge Gutiérrez; Enrique García-Villa; Rodolfo Ocadiz-Delgado; Enoc M. Cortés-Malagón; Juan Vázquez; Alejandra Roman-Rosales; Elizabeth Alvarez-Rios; Haydar Celik; Marta C. Romano; Aykut Üren; Paul F. Lambert; Patricio Gariglio (Molecular and Cellular Biochemistry, 2015)

Soy glyceollins regulate transcript abundance in the female mouse brain - Sanaya F. Bamji; Robert B. Page; Dharti Patel; Alexia Sanders; Alejandro R. Alvarez; Caitlin Gambrell; Kuntesh Naik; Ashwin M. Raghavan; Matthew E. Burow; Stephen M. Boue; Carolyn M. Klinge; Margarita Ivanova; et al. (Functional & Integrative Genomics, 2015)

Detection and partial genome sequence of a new umbra-like virus of papaya discovered in Ecuador - D. F. Quito-Avila; R. A. Alvarez; M. A. Ibarra; R. R. Martin (European Journal of Plant Pathology, 2015)

Changes in metal contents in shrimp cultured in NW Mexico (2000–2010) - M. G. Frías-Espericueta; J. I. Osuna-López; C. G. Delgado-Alvarez; M. D. Muy-Rangel; G. López-López; G. Izaguirre-Fierro; F. Jaimes-Bustamante; H. M. Zazueta-Padilla; M. Aguilar-Juárez; W. Rubio-Carrasco; D. Voltolina (Environmental Monitoring and Assessment, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

Topo-Iberia project: CGPS crustal velocity field in the Iberian Peninsula and Morocco - J. Garate; J. Martin-Davila; G. Khazaradze; A. Echeverria; E. Asensio; A. J. Gil; M. C. de Lacy; J. A. Armenteros; A. M. Ruiz; J. Gallastegui; F. Alvarez-Lobato; C. Ayala; et al. (GPS Solutions, 2015)

Comparative Analysis of on-Farm Reservoir Management Techniques and Their Effect on Filtering Requirements for Irrigation - V. Martínez-Alvarez; J. F. Maestre-Valero (Water Resources Management, 2015)

HER2 and β-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations - F. Darío Cuello-Carrión; Jorge E. Shortrede; Daiana Alvarez-Olmedo; Niubys Cayado-Gutiérrez; Gisela N. Castro; Felipe C. M. Zoppino; Martín Guerrero; Estefania Martinis; Rodolfo Wuilloud; Nidia N. Gómez; Verónica Biaggio; Javier Orozco; et al. (Clinical & Experimental Metastasis, 2015)

Use of ground-penetrating radar for construction monitoring and evaluation of perpetual pavements - Jiusu Li; Lubinda F. Walubita; Geoffrey S. Simate; Allex E. Alvarez; Wenting Liu (Natural Hazards, 2015)

Spatial and temporal variation in superfoetation and related life history traits of two viviparous fishes: Poeciliopsis gracilis and P. infans - Patricia Frías-Alvarez; Constantino Macías Garcia; Luis F. Vázquez-Vega; J. Jaime Zúñiga-Vega (The Science of Nature, 2014)

Assessment of nutrient returns in a tropical dry forest after clear-cut without burning - L. B. Amorim; I. H. Salcedo; F. G. C. Pareyn; I. .A. Alvarez (Nutrient Cycling in Agroecosystems, 2014)

MiRNA Profile in the Substantia Nigra of Parkinson’s Disease and Healthy Subjects - Lucía F. Cardo; Eliecer Coto; René Ribacoba; Manuel Menéndez; Germán Moris; Esther Suárez; Victoria Alvarez (Journal of Molecular Neuroscience, 2014)

Influence of depth and geological structure on the transmission of blast vibrations - C. González-Nicieza; M. I. Álvarez-Fernandez; A. E. Alvarez-Vigil; D. Arias-Prieto; F. López-Gayarre; F. L. Ramos-Lopez (Bulletin of Engineering Geology and the Environment, 2014)

Detection and occurrence of melon yellow spot virus in Ecuador: an emerging threat to cucurbit production in the region - D. F. Quito-Avila; E.L. Peralta; R.R. Martin; M.A. Ibarra; R.A. Alvarez; A. Mendoza; M. Insuasti; J. Ochoa (European Journal of Plant Pathology, 2014)

Erratum to: Biocontrol and PGPR Features in Native Strains Isolated from Saline Soils of Argentina - Analía Príncipe; Florencia Alvarez; Marina G. Castro; Lucía F. Zacchi; Sonia E. Fischer; Gladys B. Mori; Edgardo Jofré (Current Microbiology, 2014)

A raspberry bushy dwarf virus isolate from Ecuadorean Rubus glaucus contains an additional RNA that is a rearrangement of RNA-2 - D. F. Quito-Avila; M. A. Ibarra; R. Alvarez; E. L. Peralta; R. R. Martin (Archives of Virology, 2014)

Detection of enteric pathogens in Turkey flocks affected with severe enteritis, in Brazil - Joelma Moura-Alvarez; Luis F. N. Nuñez; Claudete S. Astolfi-Ferreira; Terezinha Knöbl; Jorge L. Chacón; Andrea M. Moreno; Richard C. Jones; Antonio J. Piantino Ferreira (Tropical Animal Health and Production, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Antidepressant prescribing in five European countries: application of common definitions to assess the prevalence, clinical observations, and methodological implications - V. Abbing-Karahagopian; C. Huerta; P. C. Souverein; F. de Abajo; H. G. M. Leufkens; J. Slattery; Y. Alvarez; M. Miret; M. Gil; B. Oliva; U. Hesse; G. Requena; et al. (European Journal of Clinical Pharmacology, 2014)

Physical forcing and physical/biochemical variability of the Mediterranean Sea: a review of unresolved issues and directions for future research - P. Malanotte-Rizzoli; V. Artale; G. L. Borzelli-Eusebi; S. Brenner; A. Crise; M. Gacic; N. Kress; S. Marullo; M. Ribera d'Alcalà; S. Sofianos; T. Tanhua; A. Theocharis; et al. (Ocean Science, 2014)
This paper is the outcome of a workshop held in Rome in November 2011 on the occasion of the 25th anniversary of the POEM (Physical Oceanography of the Eastern Mediterranean) program. In the workshop discussions, a number of unresolved issues were identified for the physical and biogeochemical properties of the Mediterranean Sea as a whole, i.e., comprising the Western and Eastern sub-basins. Over the successive two years, the related ideas were discussed among the group of scientists who participated in the workshop and who have contributed to the writing of this paper. Three major topics were identified, each of them being the object of a section divided into a number of different sub-sections, each addressing a specific physical, chemical or biological issue: 1. Assessment of basin-wide physical/biochemical properties, of their variability and interactions. 2. Relative importance of external forcing functions (wind stress, heat/moisture fluxes, forcing through straits) vs. internal variability. 3. Shelf/deep sea interactions and exchanges of physical/biogeochemical properties and how they affect the sub-basin circulation and property distribution. Furthermore, a number of unresolved scientific/methodological issues were also identified and are reported in each sub-section after a short discussion of the present knowledge. They represent the collegial consensus of the scientists contributing to the paper. Naturally, the unresolved issues presented here constitute the choice of the authors and therefore they may not be exhaustive and/or complete. The overall goal is to stimulate a broader interdisciplinary discussion among the scientists of the Mediterranean oceanographic community, leading to enhanced collaborative efforts and exciting future discoveries.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Mesozoic exhumation history and palaeolandscape of the Iberian Massif in eastern Galicia from apatite fission-track and (U+Th)/He data - R. W. Grobe; J. Alvarez-Marrón; U. A. Glasmacher; F. M. Stuart (International Journal of Earth Sciences, 2014)

Biochemical approaches to C4 photosynthesis evolution studies: the case of malic enzymes decarboxylases - Mariana Saigo; Marcos A. Tronconi; Mariel C. Gerrard Wheeler; Clarisa E. Alvarez; María F. Drincovich; Carlos S. Andreo (Photosynthesis Research, 2013)

Mutational Screening of PARKIN Identified a 3′ UTR Variant (rs62637702) Associated with Parkinson’s Disease - Lorena de Mena; LLuís Samaranch; Eliecer Coto; Lucía F. Cardo; René Ribacoba; Oswaldo Lorenzo-Betancor; Pau Pastor; Li Wang; Jaione Irigoyen; Ignacio F. Mata; Marta Díaz; Germán Moris; et al. (Journal of Molecular Neuroscience, 2013)

Kinetics and functional diversity among the five members of the NADP-malic enzyme family from Zea mays, a C4 species - Clarisa E. Alvarez; Mariana Saigo; Ezequiel Margarit; Carlos S. Andreo; María F. Drincovich (Photosynthesis Research, 2013)

Socio-Economic Impact of Evaporation Losses from Reservoirs Under Past, Current and Future Water Availability Scenarios in the Semi-Arid Segura Basin - J. F. Maestre-Valero; D. Martínez-Granados; V. Martínez-Alvarez; J. Calatrava (Water Resources Management, 2013)

Lipid storage in high-altitude Andean Lakes extremophiles and its mobilization under stress conditions in Rhodococcus sp. A5, a UV-resistant actinobacterium - Susana Bequer Urbano; Virginia H. Albarracín; Omar F. Ordoñez; María E. Farías; Héctor M. Alvarez (Extremophiles, 2013)

The Western Mediterranean summer variability and its feedbacks - M. J. OrtizBeviá; F. J. Alvarez-García; A. M. Ruiz de Elvira; G. Liguori; J. H. Carretero (Climate Dynamics, 2012)

Cadmium and Lead Concentrations in the Fish Tissues of a Coastal Lagoon System of the SE Gulf of California - J. M. Quintero-Alvarez; M. F. Soto-Jiménez; F. Amezcua; D. Voltolina; M. G. Frías-Espericueta (Bulletin of Environmental Contamination and Toxicology, 2012)

Overproduction of the multidrug efflux pump MexEF‐OprN does not impair Pseudomonas aeruginosa fitness in competition tests, but produces specific changes in bacterial regulatory networks - Jorge Olivares; Carolina Alvarez‐Ortega; Juan F. Linares; Fernando Rojo; Thilo Köhler; José Luis Martínez (Environmental Microbiology, 2012)
Summary It is generally assumed that acquisition of antibiotic resistance leads to non‐specific fitness costs. We have tested the alternative hypothesis that acquisition of antibiotic resistance may not always produce a general burden to the microorganisms, as measured in competition tests, but rather lead to specific changes in bacterial physiology. To this end we studied the effect of overproducing the multidrug efflux pump MexEF‐OprN on Pseudomonas aeruginosa due to a constitutive activation of MexT, the transcriptional activator of the mexEF‐oprN genes. We found that overexpression of MexEF‐OprN does not cause a significant decrease in P. aeruginosa fitness in classical competition tests, indicating the absence of a large metabolic burden and that any possible negative effects might be observed only under specific conditions. Transcriptomic analyses revealed that overexpression of MexEF‐OprN results in reduced expression of several quorum‐sensing regulated genes. We traced back this phenotype to a delay in PQS production due to extrusion of kynurenine, a PQS precursor, through the efflux pump. Type VI secretion was also impaired. A Caenorhabditis elegans model demonstrated that overproduction of MexEF‐OprN impairs virulence in P. aeruginosa . This effect was mainly due to the activity of the efflux pump, and not to MexT, despite the fact that the latter regulates Type III and Type VI secretion. Altogether, these data indicate that antibiotic resistance can produce modifications in the bacterial regulatory networks with relevant consequences for the bacterial behaviour in specific ecosystems, including the infected host.

A Search for SNCA 3′ UTR Variants Identified SNP rs356165 as a Determinant of Disease Risk and Onset Age in Parkinson’s Disease - Lucía F. Cardo; Eliecer Coto; Lorena de Mena; René Ribacoba; Oswaldo Lorenzo-Betancor; Pau Pastor; LLuis Samaranch; Ignacio F. Mata; Marta Díaz; Germán Moris; Manuel Menéndez; Ana I. Corao; et al. (Journal of Molecular Neuroscience, 2012)

Diversity of Brazilian biovar 2 strains of Ralstonia solanacearum - Bárbara G. Santana; Carlos A. Lopes; Elba Alvarez; Cristine C. Barreto; Caitilyn Allen; Betania F. Quirino (Journal of General Plant Pathology, 2012)

Litterfall dynamics in carbonate and deltaic mangrove ecosystems in the Gulf of Mexico - Carlos Coronado-Molina; H. Alvarez-Guillen; J. W. Day; E. Reyes; B. C. Perez; F. Vera-Herrera; R. Twilley (Wetlands Ecology and Management, 2012)

Digestive enzyme activities during early ontogeny in Common snook (Centropomus undecimalis) - L. D. Jimenez-Martinez; C. A. Alvarez-González; D. Tovar-Ramírez; G. Gaxiola; A. Sanchez-Zamora; F. J. Moyano; F. J. Alarcón; G. Márquez-Couturier; E. Gisbert; W. M. Contreras-Sánchez; N. Perales-García; L. Arias-Rodríguez; et al. (Fish Physiology and Biochemistry, 2012)

S-Wave Velocities of the Lithosphere–Asthenosphere System in the Caribbean Region - O’Leary F. González; José Leonardo Alvarez; Bladimir Moreno; Giuliano F. Panza (Pure and Applied Geophysics, 2012)

Synthesis of Temperature-Responsive Dextran-MA/PNIPAAm Particles for Controlled Drug Delivery Using Superhydrophobic Surfaces - Ana Catarina Lima; Wenlong Song; Barbara Blanco-Fernandez; Carmen Alvarez-Lorenzo; João F. Mano (Pharmaceutical Research, 2011)

Residual concentrations of the flukicidal compound triclabendazole in dairy cows’ milk and cheese - F. Imperiale; P. Ortiz; M. Cabrera; C. Farias; J.M. Sallovitz; S. Iezzi; J. Pérez; L. Alvarez; C. Lanusse (Food Additives & Contaminants: Part A, 2011)

Development of digestive enzymes in larvae of Mayan cichlid Cichlasoma urophthalmus - G. López-Ramírez; C. A. Cuenca-Soria; C. A. Alvarez-González; D. Tovar-Ramírez; J. L. Ortiz-Galindo; N. Perales-García; G. Márquez-Couturier; L. Arias-Rodríguez; J. R. Indy; W. M. Contreras-Sánchez; E. Gisbert; F. J. Moyano (Fish Physiology and Biochemistry, 2011)

Seasonal physiological plasticity and recovery capacity after summer stress in Mediterranean scrub communities - M. Zunzunegui; Maria Cruz Díaz Barradas; F. Ain-Lhout; L. Alvarez-Cansino; M. P. Esquivias; F. García Novo (Plant Ecology, 2011)

Influence of the KDEL signal, DMSO and mannitol on the production of the recombinant antibody 14D9 by long-term Nicotiana tabacum cell suspension culture - J. López; F. Lencina; S. Petruccelli; P. Marconi; M. A. Alvarez (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Assessment of enzymatic efficiency on protein digestion in the tilapia Oreochromis niloticus - A. Uscanga; F. J. Moyano; C. A. Alvarez (Fish Physiology and Biochemistry, 2010)

High population differentiation in the rock-dwelling land snail (Trochulus caelatus) endemic to the Swiss Jura Mountains - Sylvain Ursenbacher; Caren Alvarez; Georg F. J. Armbruster; Bruno Baur (Conservation Genetics, 2010)

Development of digestive enzyme activity in larvae of spotted sand bass Paralabrax maculatofasciatus II: Electrophoretic analysis - C. A. Alvarez-González; F. J. Moyano-López; R. Civera-Cerecedo; V. Carrasco-Chávez; J. L. Ortíz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; S. Dumas (Fish Physiology and Biochemistry, 2010)

Risk factors for multidrug-resistant Pseudomonas aeruginosa acquisition. Impact of antibiotic use in a double case–control study - M. Montero; M. Sala; M. Riu; F. Belvis; M. Salvado; S. Grau; J. P. Horcajada; F. Alvarez-Lerma; R. Terradas; M. Orozco-Levi; X. Castells; H. Knobel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Integrating the multiple dimensions of genomic and epigenomic landscapes of cancer - Raj Chari; Kelsie L. Thu; Ian M. Wilson; William W. Lockwood; Kim M. Lonergan; Bradley P. Coe; Chad A. Malloff; Adi F. Gazdar; Stephen Lam; Cathie Garnis; Calum E. MacAulay; Carlos E. Alvarez; et al. (Cancer and Metastasis Reviews, 2010)

Pharmacological effects of two cytolysins isolated from the sea anemone Stichodactyla helianthus - T. García; D. Martinez; A. Palmero; C. Soto; M. Tejuca; F. Pazos; R. Menéndez; C. Alvarez; A. Garateix (Journal of Biosciences, 2009)

Does the disturbance hypothesis explain the biomass increase in basin‐wide Amazon forest plot data? - M. GLOOR; O. L. PHILLIPS; J. J. LLOYD; S. L. LEWIS; Y. MALHI; T. R. BAKER; G. LÓPEZ‐GONZALEZ; J. PEACOCK; S. ALMEIDA; A. C. ALVES De OLIVEIRA; E. ALVAREZ; I. AMARAL; et al. (Global Change Biology, 2009)
Positive aboveground biomass trends have been reported from old‐growth forests across the Amazon basin and hypothesized to reflect a large‐scale response to exterior forcing. The result could, however, be an artefact due to a sampling bias induced by the nature of forest growth dynamics. Here, we characterize statistically the disturbance process in Amazon old‐growth forests as recorded in 135 forest plots of the RAINFOR network up to 2006, and other independent research programmes, and explore the consequences of sampling artefacts using a data‐based stochastic simulator. Over the observed range of annual aboveground biomass losses, standard statistical tests show that the distribution of biomass losses through mortality follow an exponential or near‐identical Weibull probability distribution and not a power law as assumed by others. The simulator was parameterized using both an exponential disturbance probability distribution as well as a mixed exponential–power law distribution to account for potential large‐scale blowdown events. In both cases, sampling biases turn out to be too small to explain the gains detected by the extended RAINFOR plot network. This result lends further support to the notion that currently observed biomass gains for intact forests across the Amazon are actually occurring over large scales at the current time, presumably as a response to climate change.

Influence of Helicobacter pylori infection on the expression of MLH1 and MGMT in patients with chronic gastritis and gastric cancer - W. Bartchewsky; M. R. Martini; A. C. Squassoni; M. C. Alvarez; M. S. P. Ladeira; D. M. F. Salvatore; M. A. Trevisan; J. Pedrazzoli; M. L. Ribeiro (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Mutation update of spinal muscular atrophy in Spain: molecular characterization of 745 unrelated patients and identification of four novel mutations in the SMN1 gene - Laura Alías; Sara Bernal; Pablo Fuentes-Prior; María Jesus Barceló; Eva Also; Rebeca Martínez-Hernández; Francisco J. Rodríguez-Alvarez; Yolanda Martín; Elena Aller; Elena Grau; Ana Peciña; Guillermo Antiñolo; et al. (Human Genetics, 2009)

Development of digestive enzyme activity in larvae of spotted sand bass Paralabrax maculatofasciatus. 1. Biochemical analysis - C. A. Alvarez-González; F. J. Moyano-López; R. Civera-Cerecedo; V. Carrasco-Chávez; J. L. Ortiz-Galindo; S. Dumas (Fish Physiology and Biochemistry, 2008)

Quantitative second harmonic generation imaging of cartilage damage - Kelvin G. M. Brockbank; W. Robb MacLellan; Jiansong Xie; Sarah F. Hamm-Alvarez; Zhen Zhen Chen; Katja Schenke-Layland (Cell and Tissue Banking, 2008)

Maize cytosolic NADP-malic enzyme (ZmCytNADP-ME): a phylogenetically distant isoform specifically expressed in embryo and emerging roots - Enrique Detarsio; Verónica G. Maurino; Clarisa E. Alvarez; Gabriela L. Müller; Carlos S. Andreo; María F. Drincovich (Plant Molecular Biology, 2008)

Does the Jarman–Bell principle at intra-specific level explain sexual segregation in polygynous ungulates? Sex differences in forage digestibility in Soay sheep - F. J. Pérez-Barbería; E. Pérez-Fernández; E. Robertson; B. Alvarez-Enríquez (Oecologia, 2008)

Aerobic bioremediation of chlorobenzene source-zone soil in flow-through columns: performance assessment using quantitative PCR - Rosa F. Dominguez; Marcio L. B. da Silva; Travis M. McGuire; David Adamson; Charles J. Newell; Pedro J. J. Alvarez (Biodegradation, 2008)

Crust and Upper Mantle Structure in the Caribbean Region by Group Velocity Tomography and Regionalization - O'Leary González; Leonardo Alvarez; Mariangela Guidarelli; Giuliano F. Panza (Pure and Applied Geophysics, 2007)

Flow Perfusion Improves Seeding of Tissue Engineering Scaffolds with Different Architectures - Jose F. Alvarez-Barreto; Shawna M. Linehan; Robert L. Shambaugh; Vassilios I. Sikavitsas (Annals of Biomedical Engineering, 2007)

Molecular characterization of microbial populations at two sites with differing reductive dechlorination abilities - Brian G. Rahm; Sadhana Chauhan; Victor F. Holmes; Tamzen W. Macbeth; Kent S. Jr. Sorenson; Lisa Alvarez-Cohen (Biodegradation, 2006)

Identification of type-specific and cross-reactive neutralizing conformational epitopes on the major capsid protein of human papillomavirus type 31 - M. J. J. Fleury; A. Touzé; E. Alvarez; G. Carpentier; C. Clavel; J.-F. Vautherot; P. Coursaget (Archives of Virology, 2006)

Ecophysiology, growth timing and reproductive effort of three sexual foms of Corema album (Empetraceae) - M. Zunzunegui; M.C. Díaz Barradas; A. Clavijo; L. Alvarez Cansino; F. Ain Lhout; F. García Novo (Plant Ecology, 2006)

Parallels in the evolution of the two largest New and Old World seed‐beetle genera (Coleoptera, Bruchidae) - G. J. KERGOAT; N. ALVAREZ; M. HOSSAERT‐MCKEY; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2005)
This study provides the first phylogenetic analysis of a large sample of the two largest genera of seed‐beetles, Acanthoscelides Schilsky and Bruchidius Schilsky, which mostly feed on legumes (Fabaceae). The goal of this study was to investigate evolutionary patterns in relation to biogeography and host‐plant associations. We used three mitochondrial molecular markers and parsimony and Bayesian inference methods to reconstruct the phylogeny of 76 species. In addition, we critically reviewed host‐plant records in the literature for these two bruchid genera. Our results demonstrated the existence of two major clades, one New World and one largely Old World, which generally correspond to the two genera. Yet, current classification of several species is erroneous, so that both genera as currently defined are paraphyletic. We highlighted a strong trend toward specialization (with high taxonomic conservatism in host‐plant use) exhibited by the two studied genera. However, we showed the existence of several host shifts during the evolution of this group of bruchids. Our phylogenetic hypotheses and our evaluation of host‐plant associations both suggest that the two genera have undergone parallel evolution, as they have independently colonized similar host plants in their respective areas of distribution. Our estimation of divergence times indicated a more ancient origin for bruchids than that suggested by the fossil records. Interestingly, the suggested timing of diversification is consistent with the hypothesis of a radiation that could have occurred contemporaneously with the diversification of their legume hosts.

Molecular Confirmation of the Position of Gossypium trifurcatum Vollesen - Ryan A. Rapp; Ines Alvarez; Jonathan F. Wendel (Genetic Resources and Crop Evolution, 2005)

Within-family genetic variation and epistasis in cassava (Manihot esculenta Crantz) adapted to the acid-soils environment - J. C. Perez; H. Ceballos; F. Calle; N. Morante; W. Gaitán; G. Llano; E. Alvarez (Euphytica, 2005)

Diallel inheritance of relevant traits in cassava (Manihot esculenta Crantz) adapted to acid-soil savannas - F. Calle; J. C. Perez; W. Gaitán; N. Morante; H. Ceballos; G. Llano; E. Alvarez (Euphytica, 2005)

Spatial Distribution, Scaling and Self-similar Behavior of Fracture Arrays in the Los Planes Fault, Baja California Sur, Mexico - A. F. Nieto-Samaniego; S. A. Alaniz-Alvarez; G. Tolson; K. Oleschko; G. Korvin; S. S. Xu; J. A. Prez-Venzor (Pure and Applied Geophysics, 2005)

Stable Transfection of MDCK Cells with Epitope-Tagged Human PepT1 - Chun Chu; Curtis T. Okamoto; Sarah F. Hamm-Alvarez; Vincent H. L. Lee (Pharmaceutical Research, 2004)

Application of Lead Isotopic Ratios in Atmospheric Pollution Studies in the Valley of Mexico - T. Martinez; J. Lartigue; F. Juarez; P. Avila-Perez; G. Zarazua; C. Marquez; M. P. Orta; V. Alvarez (Journal of Atmospheric Chemistry, 2004)

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Ground Motion Zoning of Santiago de Cuba: An Approach by SH Waves Modelling - Leonardo Alvarez; Julio Garca; Franco Vaccari; Giuliano F. Panza; Bertha Gonzlez; Carmen Reyes; Brbara Fernndez; Ramn Pico; Jos A. Zapata; Enrique Arango (Pure and Applied Geophysics, 2004)

Characterization of the First VanB Vancomycin-Resistant Enterococcus faecium Isolated in a Spanish Hospital - Fabin Lorenzo-Daz; Teresa Delgado; Jos A. Reyes-Darias; Carlos Flores; Sebastin Mndez-Alvarez; Jess Villar; Antonio Sierra; Flix Claverie-Martn (Current Microbiology, 2004)

Production of a fusion protein consisting of the enterotoxigenic Escherichia coli heat-labile toxin B subunit and a tuberculosis antigen in Arabidopsis thaliana - M. M. Rigano; M. L. Alvarez; J. Pinkhasov; Y. Jin; F. Sala; C. J. Arntzen; A. M. Walmsley (Plant Cell Reports, 2004)

Redox-related peroxidative responses evoked by methyl-jasmonate in axenically cultured aeroponic sunflower ( Helianthus annuus L . ) seedling roots - I. Garrido; F. Espinosa; M. C. Crdoba-Pedregosa; J. A. Gonzlez-Reyes; M. C. Alvarez-Tinaut (Protoplasma, 2003)

Effects of Early Contact with Maternal Parent on Locomotor Activity and Exploratory Behavior in Spiderlings of Hogna carolinensis (Araneae: Lycosidae) - F. Punzo; J. Alvarez (Journal of Insect Behavior, 2002)

Assessment of in-situ bioremediation at a refinery waste-contaminated site and an aviation gasoline contaminated site - Vishvesh K. Bhupathiraju; Paula Krauter; Hoi-Ying N. Holman; Mark E. Conrad; Paul F. Daley; Alexis S. Templeton; James R. Hunt; Mark Hernandez; Lisa Alvarez-Cohen (Biodegradation, 2002)

MADS-box gene expression in lateral primordia, meristems and differentiated tissues of Arabidopsis thaliana roots - Caroline Burgeff; Sarah J. Liljegren; Rosalinda Tapia-López; Martin F. Yanofsky; Elena R. Alvarez-Buylla (Planta, 2002)

Inoculation of containerized Pinus pinea L. seedlings with seven ectomycorrhizal fungi - Ana Rincón; Isabel F. Alvarez; Joan Pera (Mycorrhiza, 2001)

Variation in the Sizes of Chthamalid Barnacle Post‐Settlement Cyprids on European Shores - Ruth M. O'Riordan; Jane Delany; David McGrath; Alan A. Myers; Anne Marie Power; Neil F. Ramsay; Damaso Alvarez; Teresa Cruz; Federica G. Pannacciulli; Pedro Range; Giulio Relini (Marine Ecology, 2001)
As part of a wider study on the settlement and recruitment of Chthamalus spp. in Europe, this study investigated whether chthamalid cyprids can be separated by length on a European scale. Variation in cyprid length with latitude and temporal variation at selected localities were also examined. The lengths of cyprids collected between 1996 – 1999 on nine rocky shores in Europe are reported. Elminius modestus cyprids were found only at Roscoff, NW France and could be distinguished due to their carapace shape and length. They showed a unimodal length distribution, measuring between 450 and 625 µm, with no variation in length between the two sampling dates (1997 and 1998). Based on carapace shape and length, the remaining cyprids in the collections were identified as one of three chthamalid species, Chthamalus montagui, Chthamalus stellatus or Euraphia depressa. Bimodal length distributions of chthamalid cyprids were seen on some shores, while others had a single small‐sized modal group (representing C. montagui on Atlantic shores and/or E. depressa in the Mediterranean) separated from a few distinctly larger cyprids ( C. stellatus ). Metamorphs collected simultaneously with cyprid collections were identified as C. stellatus or C. montagui , except at Roscoff, where E. modestus were also found. In southern Portugal, where all metamorphs collected were C. montagui and adult C. montagui were the dominant barnacles, most cyprids measured between 350 and 550 µm long and this size distribution coincides with the distribution expected for C. montagui. Cyprids collected on these four more southerly Portuguese shores had the same modal length class (475 µm) and this remained constant between successive years at Luz and Albufeira, Algarve. The smallest (350 µm long) wild chthamalid cyprids found were from southern Portugal and Italy. In Spain, France and Ireland the smallest chthamalid cyprid was 425 µm long. The results from the present study support the hypothesis that on Atlantic shores cyprids of C. montagui can be separated from those of C. stellatus based on size, although there is some variation in cyprid length with latitude as well as temporal variation at selected localities.

Influence of type II 5′ deiodinase on TSH content in diabetic rats - C. Aláez; R. Calvo; M. J. Obregón; C. Alvarez; L. Goya; F. Escrivá; M. A. Martín; A. M. Pascual-Leone (Journal of Physiology and Biochemistry, 2001)

Effect of dichlorophenolindophenol, dichlorophenolindophenol-sulfonate, and cytochromec on redox capacity and simultaneous net H+/K+ fluxes in aeroponically grown seedling roots of sunflower (Helianthus annuus L.): New evidence for a plasma membrane CN?-resistant redox chain - I. Garrido; F. Espinosa; M. C. Alvarez-Tinaut (Protoplasma, 2001)

Nocodazole Treatment of CV-1 Cells Enhances Nuclear/Perinuclear Accumulation of Lipid-DNA Complexes and Increases Gene Expression - Jimmy Lindberg; Mary Ann M. Fernandez; J. Dezz Ropp; Sarah F. Hamm-Alvarez (Pharmaceutical Research, 2001)

Acidogenic fermentation of source separated mixtures of vegetables and fruits wasted from supermarkets - P. Traverso; P. Pavan; D. Bolzonella; L. Innocenti; F. Cecchi; J. Mata-Alvarez (Biodegradation, 2000)

Helminth parasite communities of the conger eel in the estuaries of Arousa and Muros (Galicia, north‐west Spain) - M. L. Sanmartín; M. F. Alvarez; D. Peris; R. Iglesias; J. Leiro (Journal of Fish Biology, 2000)
The nematodes Cucullanus hians, Cucullanus longispiculum , Cucullanus minutus , Contracaecum sp., Anisakis simplex , and Cristitectus congeri , the cestodes Grillotia , sp. and Scolex pleuronectis , and the acanthocephalan Acanthocephaloides propinquus , were recorded from 251 conger eels from the Muros and Arousa estuaries, north‐west Spain. Several species were useful as tags and showed that conger eels in both estuaries and also on the continental shelf belong to separate populations. The nematode C. congeri , shows a distribution pattern indicating that the trophic chains involving the conger eel in each estuary are probably different. The species composition and abundance of the nematode, cestode and acanthocephalan fauna of Conger conger , on the north‐west Spanish coast may depend more on population isolation and variations in trophic chains between the sites studied than on the particular environmental conditions of the sites.

Risk Factors for Esophageal Candidiasis - A. Chocarro Martínez; F. Galindo Tobal; G. Ruiz-Irastorza; A. González López; F. Alvarez Navia; C. Ochoa Sangrador; M.I. Martín Arribas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Lack of Evolutionary Divergence in Courtship Songs of Drosophila pseudoobscura Subspecies - Mohamed A. F. Noor; Marcus A. Williams; Diana Alvarez; Manuel Ruiz-García (Journal of Insect Behavior, 2000)

Evidence for the induction of apoptosis by endosulfan in a human T-cell leukemic line - Krishnaswamy Kannan; Randall F. Holcombe; Sushil K Jain; Xavier Alvarez-Hernandez; Robert Chervenak; Robert E Wolf; Jonathan Glass (Molecular and Cellular Biochemistry, 2000)

5-HT 3 - and 5-HT 2C -antagonist properties of cyamemazine: significance for its clinical anxiolytic activity - M. Alvarez-Guerra; F. d'Alch-Bire; W. A. Wolf; F. Vargas; M. Dib; R. P. Garay (Psychopharmacology, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Deterministic Seismic Zoning of Eastern Cuba - L. Alvarez; F. Vaccari; G. F. Panza (Pure and Applied Geophysics, 1999)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

G disulphide bond native conformation is required to elicit trout neutralizing antibodies against VHSV - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; J. M. Coll (Journal of Fish Diseases, 1999)

Geochemistry of Aluminium and Iron in Mine Soils from As Pontes, Galicia (N.W. Spain) - C. Monterroso; F. Macías; E. Alvarez; M. L. Fernández-Marcos (Water, Air, & Soil Pollution, 1999)

Coinoculation of containerized Douglas-fir ( Pseudotsuga menziesii ) and maritime pine ( Pinus pinaster ) seedlings with the ectomycorrhizal fungi Laccaria bicolor and Rhizopogon spp. - J. Parladé; I. F. Alvarez; J. Pera (Mycorrhiza, 1999)

Phenotypic variability in different strains of Pseudomonas syringae subsp. savastanoi isolated from different hosts - F. Alvarez; J.E. García de los Ríos; P. Jimenez; A. Rojas; P. Reche; M.T. Troya (European Journal of Plant Pathology, 1998)

Effect of some electron donors and acceptors on redox capacity and simultaneous net H+/K+ fluxes by aeroponic sunflower seedling roots: Evidence for a CN?-resistant redox chain accessible to nonpermeative redox compounds - I. Garrido; F. Espinosa; M. A. Paredes; M. C. Alvarez-Tinaut (Protoplasma, 1998)

Hydrodynamic and chemical conditions during onset of a red-tide assemblage in an estuarine upwelling ecosystem - X. A. Alvarez-Salgado; F. G. Figueiras; M. L. Villarino; Y. Pazos (Marine Biology, 1998)

Sequencing and characterization of the coat protein and 3′ non-coding region of a newsweet potato potyvirus - V. Alvarez; D. A. Ducasse; E. Biderbost; S. F. Nome (Archives of Virology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Immobilized Lotus tetragonolobus agglutinin binds oligosaccharides containing the Lex determinant - Liying Yan; Patricia P Wilkins; Gerardo Alvarez-Manilla; Su-Il Do; David F Smith; Richard D Cummings (Glycoconjugate Journal, 1997)